Metacognitive Reading Strategies in EFL Context: A Systematic Literature Review - Delti Yulita; Merlin H. Napitupulu (Indonesian Educational Research Journal, 2023)
This article aims to synthesize the overall research on metacognitive reading strategies in EFL context. The method used is the Systematic Literature Review to read and to examine the studies related metacognitive reading strategies in the last two decades. associated major theme in metacognitive reading strategies in EFL and is divided into three themes, those are (1) metacognitive strategies towards EFL reading; (2) assessing metacognitive reading strategies; and (3) metacognitive reading strategies for diverse learners. The results shown that the use of some metacognitive strategies in teaching reading could improve students’ reading comprehension as well as students’ reading behavior. Meanwhile, the importance of cultural, linguistic and educational background variation affects students’ metacognitive strategies during reading, specifically academic text and school materials. Lastly, the learners tended to utilize similar strategic awareness in reading due the difference sociocultural environment.